(untitled) (Sains Humanika, 2025)
Seeking counselling help is an essential strategy for addressing mental health issues, particularly among university students who face various academic and personal challenges. This research examines help-seeking behaviour for counselling among university students from China. A systematic search of electronic databases, including PubMed, PsycINFO, CNKI, and Google Scholar was conducted following the PRISMA guidelines. Search terms included "Chinese university students" AND "counselling" OR "mental health help" OR "mental health service" AND "mental health" AND "help-seeking" OR "seeking help" AND "barriers to seeking counselling" OR "challenges in seeking counselling." The research was limited to peer-reviewed articles published between 2010 and 2024. Quality assessment was performed on the identified studies. Based on the selection criteria, 32 articles, met the inclusion criteria. Of these, 23 studies employed quantitative methods; one used a cohort design, three used qualitative methods, one used mixed methods, and four used experimental designs. Drawing on data from 39,495 participants, the analysis revealed the prevalence of help-seeking, the barriers to help-seeking and the interventions implemented. Findings suggest that help-seeking for counselling among Chinese university students is relatively low. The decision to seek help is influenced by a complex interplay of barriers, including attitudes, stigma, mental health literacy, and other facilitators. Additionally, cultural factors play a significant role in shaping help-seeking behaviours. Future research should focus on experimental studies to better understand trends in help-seeking behaviour and to develop high-reliability and high-validity intervention programmes that account for cultural influences.